Thermacut bur gingivectomy versus functional crown lengthening in management of subgingival interproximal carious lesions 12 months randomized controlled trial - Ahmed Khairy Elmorsy; Shereen Hafez Ibrahim; Hani Mohamed Essam El-Nahass; Nesma Shemais; Ahmed El Zohairy (Scientific Reports)
Abstract This clinical trial aimed to evaluate acquiring deep subgingival interproximal carious lesions by the mean of Thermacut bur gingivectomy, versus functional crown lengthening procedure. A total of 30 deep proximal cavities in posterior teeth were randomly assigned into two groups (n = 15); Thermacut Bur Gingivectomy (TBG) or Functional Crown Lengthening (FCL). Patient Satisfaction using a Visual Analog Scale (VAS) as a primary outcome. Bleeding on Probing (BoP), Probing Depth (PD), and Crestal Bone Level (CBL) as secondary outcomes, and Marginal Integrity using Modified USPHS Criteria as a tertiary outcome, were evaluated at the baseline, immediate postoperative, 6-month, and 1-year follow-up intervals. There was a statistically significant difference between the two groups regarding patient satisfaction in the immediate postoperative values, no statistically significant difference was found in the 6-month and 12-month intervals. Regarding BoP, no statistical significance was found between intervention and control groups at different time intervals. Regarding PD, Pre- and after 6 months, there was no significant difference in values measured in both groups, after 1 year, values measured in the intervention group were statistically significant, Regarding CBL, there was no significant difference in bone levels measured in both groups at baseline. However, in other intervals, values measured in the control group were significantly higher than those in the intervention group. Regarding Marginal Integrity, no significant differences were found between both groups at any time interval. Both Thermacut bur gingivectomy and functional crown lengthening techniques are valid treatments for the management of deep subgingival interproximal carious lesions in vital teeth. However, Thermacut bur was superior to functional crown lengthening in terms of preserving the alveolar bone crest. Clinical Significance: Thermacut bur gingivectomy is an alternative to solve the shortcomings of functional crown lengthening.